Evolution of the β-lactam-resistant Streptococcus pneumoniae PMEN3 clone over a 30 year period in Barcelona, Spain. (27th August 2018) - Càmara, Jordi; Cubero, Meritxell; Martín-Galiano, Antonio J; García, Ernesto; Grau, Imma; Nielsen, Jesper B; Worning, Peder; Tubau, Fe; Pallarés, Román; Domínguez, M Ángeles; Kilian, Mogens; Liñares, Josefina; et al.
Abstract: Objectives: To analyse the epidemiology and genetic evolution of PMEN3 (Spain 9V -156), a penicillin-non-susceptible clone of Streptococcus pneumoniae, causing invasive pneumococcal disease (IPD) in Barcelona during 1987–2016. Methods: WGS was performed on 46 representative isolates and the data were used to design additional molecular typing methods including partial MLST, PCR-RFLP and detection of surface-exposed proteins and prophages, to assign the remaining isolates to lineages. The isolates were also subjected to antimicrobial susceptibility testing. Results: Two hundred and twenty-seven adult cases of IPD caused by PMEN3 were identified. PMEN3 caused mainly pneumonia (84%) and the 30 day mortality rate was 23.1%. Evidence of recombination events was found, mostly in three regions, namely the capsular operon (associated with capsular switching) and adjacent regions containing pbp2x and pbp1a, the murM gene and the pbp2b – ddl region. Some of these genetic changes generated successful new variant serotype lineages, including one of serotype 11A that is not included in the current PCV13 vaccine. Other genetic changes led to increased MICs of β-lactams. Notably, most isolates also harboured prophages coding for PblB-like proteins. Despite these adaptations, the ability of this clone to cause IPD remained unchanged over time, highlighting the importance of its core genetic background. Conclusions: Our study demonstrated successful adaptation of PMEN3 to persist over time despite the introduction of broader antibiotics and conjugate vaccines. In addition to enhancing understanding of the molecular evolution of PMEN3, these findings highlight the need for the development of non-serotype-based vaccines to fight pneumococcal infection.